Bank risk-taking, securitization, supervision and low interest rates: Evidence from the euro area and the U.S. lending standards - Angela Maddaloni; José-Luis Peydró (European Central Bank (ECB), 2010)
Using a unique dataset of the Euro area and the U.S. bank lending standards, we find that low (monetary policy) short-term interest rates soften standards, for household and corporate loans. This softening – especially for mortgages – is amplified by securitization activity, weak supervision for bank capital and too low for too long monetary policy rates. Conversely, low long-term interest rates do not soften lending standards. Finally, countries with softer lending standards before the crisis related to negative Taylor-rule residuals experienced a worse economic performance afterwards. These results help shed light on the origins of the crisis and have important policy implications.
Keywords: G01; G21; G28; E44; E5; 330; bank capital; financial stability; Lending standards; monetary policy; securitization; Kreditgeschäft; Zinspolitik; Taylor-Regel; Verbriefung; Bankenaufsicht; Bankenregulierung; EU-Staaten; USA